REPRESENTASI KEKUASAAN DALAM WACANA KELAS DI SEKOLAH MENENGAH PERTAMA - Asrianti Asrianti (Universitas Negeri Makassar, 2019)
The Representation of Power in Classroom Discourse in Junior High School. This research describes power representation in classroom discourse. A qualitative approach was used in the research. It was classified into critical situation analysis. The data were collected through (1) observation, (2) recording, and (3) field notes. The data were analyzed through Miles and Huberman mode. The results indicate that there is an authority representation in the class situation at the school, namely; (1) representation formed authority in a class situation, (2) representation of authority strategy in a class situation, and (3) representation of authority function in the class situation. The results of authority form cover forms (a) command, (b) request, (c) prohibition, and (d) suggestion. The result of authority strategy cover forms: (a) control speech, (b) use threat, (c) give the tricky question, (d) be angry/pretend to be angry. Moreover, on authority function cover forms; (a) control learning process, (b) force, (c) trusted, and (d) respected.